2002
DOI: 10.1124/jpet.302.3.1295
|View full text |Cite
|
Sign up to set email alerts
|

MT2Melatonin Receptors Are Present and Functional in Rat Caudal Artery

Abstract: In rat caudal artery, contraction to melatonin results primarily from activation of MT 1 melatonin receptors; however, the role of MT 2 melatonin receptors in vascular responses is controversial. We examined and compared the expression and function of MT 2 receptors with that of MT 1 receptors in male rat caudal artery. MT 1 and MT 2 melatonin receptor mRNA was amplified by reverse transcription-polymerase chain reaction from caudal arteries of three rat strains (i.e., Fisher, Sprague-Dawley, and Wistar). Anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
128
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(139 citation statements)
references
References 34 publications
(71 reference statements)
5
128
1
2
Order By: Relevance
“…The hormone exerts its effects both through activation of its receptors (21), through the circulating levels of the hormone or in a more autocrine/paracrine fashion near target tissues (22,23). In addition, melatonin brings about vasoconstriction through the MT1 and vasodilation through the MT2 receptors (24). It lowers cortisol secretion (25) in the adrenal cortex, similar to the action shared with insulin (23).…”
Section: Melatonin and Its Functionmentioning
confidence: 99%
“…The hormone exerts its effects both through activation of its receptors (21), through the circulating levels of the hormone or in a more autocrine/paracrine fashion near target tissues (22,23). In addition, melatonin brings about vasoconstriction through the MT1 and vasodilation through the MT2 receptors (24). It lowers cortisol secretion (25) in the adrenal cortex, similar to the action shared with insulin (23).…”
Section: Melatonin and Its Functionmentioning
confidence: 99%
“…More recently, functional assays in vitro suggested that melatonin is involved in the control of vasomotor tone and acts via receptors located in the myocytes (Masana et al, 2002) and/or in the endothelium (Geary et al, 1998;Yang et al, 2001). In another experimental model, melatonin was shown to inhibit the rolling of leukocytes on the venular endothelial layer in vivo by stimulating MT 2 melatonin receptors (Lotufo et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…10 Expression of MT 1 and MT 2 receptor mRNA was found in different parts of the cardiovascular system, such as the heart, 11 coronary artery, aorta 12 and cerebral 13 and caudal arteries. 14 In the cardiovascular system, MT 1 and MT 2 receptor proteins were found in the heart 11 and coronary artery. 15 Activation of the MT 1 receptor causes vasoconstriction in the rat caudal artery, which is believed to be involved in the thermoregulation, 16 and activation of MT 2 results in vasodilatation.…”
Section: Introductionmentioning
confidence: 99%